Comparison of Mean Retinal Nerve Fiber Layer Thickness on Optical Coherence Tomography (OCT) in Patients of Primary Open Angle Glaucoma (POAG) After Trabeculectomy vs Anti Glaucoma Medication: Retinal Nerve Fiber Layer Thickness - Latif, Sidra; Riaz, Rashida; Qamar, Anjisha; Anjum, Misra; Bibi, Irfana; Shoukat, Tahir; Zafar, Humera (Pakistan Journal of Health Sciences, 2023)
Trabeculotomy is a surgical procedure in which a fistula is created between anterior chamber and sub-conjunctival space for drainage of aqueous. Glaucoma is a chronic disease. Objective: To compare the mean retinal nerve fibre layer thickness in patients of primary open angle glaucoma after trabeculectomy versus anti glaucoma medication. Methods: This Randomized controlled study done in Institute of Ophthalmology, Eye Unit III, KEMU, Mayo Hospital, Lahore from 10th Nov 2021 to 10th May 2022. Non-Probability Convenient Sampling technique used for sample size calculation. 60 patients were selected fulfilling the inclusion and exclusion criteria. They were divided into two groups of 30 patients each. Group A patient were given topical anti-glaucoma treatment while Group B patients underwent trabeculectomy. Pre and three months post anti-glaucoma medication/trabeculectomy, OCT test was done and thickness of retinal nerve fibre layer documented. Results: In group A, mean post-treatment RNFL thickness was 0.076 ± 0.052 microns after three months of topical treatment. In group B, mean post-treatment RNFL thickness was 0.080 ± 0.0048 microns three months after trabeculectomy. Conclusions: Trabeculectomy increases the mean retinal nerve fibre layer thickness more than anti-glaucoma medication when measured on OCT.